The Educational Content Driven from Surat Fatir And Its Educational Applications within Family - Alkhawari, Najwa Ahmad Mubark (Journal of Educational and Psychological Sciences, 2021)
The aim of this research, generally, was to reveal the educational contents driven from Surat Fatir, and to clarify the most prominent educational applications driven from these contents. The descriptive and deductive approaches were used. The research dealt with the definition of the conceptual framework of the educational contents of Surat Fatir, concentrating on its social contents, then presented their applications inside family. Some of the most important results of the research are: The succession in the earth is a value that makes it a big mission for the family through developing a sense of belonging to the homeland, protecting its capabilities, taking into account the reconstruction of the earth and achieving the principle of social partnership within the community. Developing the value of social solidarity and spare other people and taking others into account would build a coherent and fraternal society. So, the believer should keep raising his children to provide a helping hand to the needy. The application of these social educational contents within the family, in word and deed, contributes to develop the level of education within the family.